Torino 2006 Winter Olympic Games: Highlight on health services organization - Chiado Piat, S.; Minniti, D.; Traversi, D.; Gianino, M. M.; Massazza, G.; Siliquini, R. (The Journal of Emergency Medicine, 2009)
Background: Mass gatherings require attention toward planning and execution of dedicated medical care. Objectives: The aims were to describe the organization and provision of medical care in the Torino 2006 Winter Olympic Games in light of the epidemiology of illnesses and injuries among athletes during this event. Methods: The organization integrated 18 medical centers operating at Olympic venues, three polyclinics inside the Olympic Villages, and 13 pre-existing Olympic Hospitals. The design was a retrospective study, with review of medical records at Olympic medical facilities. All the athletes who attended any medical center or polyclinic were eligible. The main outcomes included type of injuries and illnesses affecting athletes, incidence of injuries and illnesses by provenance and discipline, and rate of hospital admissions. Results: A total of 330 athletes received medical care and 676 medical encounter forms were documented, with an overall medical utilization rate of 12.66%. Skeleton, snowboard, bobsleigh, and alpine and freestyle skiing had the highest medical attendance rate relative to other disciplines (p < 0.001). The majority of injuries and illnesses were of a minor nature. A total of 23 visits required hospital admissions (3.40%). Conclusion: The described model of medical coverage for such events seemed to be practical and efficient for the athletes, without depleting services to the general population. The risk of severe injury and illness seemed to be low. These data could be useful for planning medical services in future mass gatherings.